A Delicate Equilibrium : Debt Relief and Default Penalties in an International Context. (IMF Working Papers; Working Paper ;, 1989)
Debt relief and penalties are discussed in connection with sovereign-country loans. We focus on conditions for the existence of penalties that are too low for ensuring Pareto efficiency, and show the possible time inconsistency of optimal debt contracts. A methodology for ascertaining debt relief implicit in international loans is outlined.